2007
DOI: 10.1021/ic700647v
|View full text |Cite
|
Sign up to set email alerts
|

Single-Boron Complexes of N-Confused and N-Fused Porphyrins

Abstract: Boron(III) has been inserted into N-confused porphyrin, (NCPH)H2 (1), and N-fused porphyrin, (NFP)H (2). The reaction of dichlorophenylborane and 1 yields sigma-phenylboron N-confused porphyrin (4). The boron atom is bound by two pyrrolic nitrogen atoms and the sigma-phenyl ligand. The N-confused pyrrole ring is not involved in the direct coordination because the C(21)-H fragment remains intact. A reaction between PhBCl2 and N-fused porphyrin produces sigma-phenylboron N-fused porphyrin (3+). 4 converts quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 47 publications
3
60
0
1
Order By: Relevance
“…As reflected from the spectral analysis, the B III in 8 is coordinated with the dipyrromethene unit and the remaining two positions are occupied by the σ‐phenyl and the chloride ion. The B−N bond lengths (B−N1 and B−N2) are 1.604(8) and 1.571(8) Å, which are longer than the B−N bond lengths reported earlier . The geometry around the boron center is tetrahedral (Supporting Information Figure S28c) and the boron(III) ion is 1.45(6) Å above the mean macrocyclic plane.…”
Section: Figurementioning
confidence: 65%
See 1 more Smart Citation
“…As reflected from the spectral analysis, the B III in 8 is coordinated with the dipyrromethene unit and the remaining two positions are occupied by the σ‐phenyl and the chloride ion. The B−N bond lengths (B−N1 and B−N2) are 1.604(8) and 1.571(8) Å, which are longer than the B−N bond lengths reported earlier . The geometry around the boron center is tetrahedral (Supporting Information Figure S28c) and the boron(III) ion is 1.45(6) Å above the mean macrocyclic plane.…”
Section: Figurementioning
confidence: 65%
“…The disappearance of inner NH (H 20) signal confirms the formation of 8 (Figure b and Supporting Information Figures S20–S22). The spectral analysis reveals that the inner CH (H 19) is shifted 2.20 ppm upfield and resonates at 5.31 ppm, suggesting a weak nonbonding interaction with the boron ion . The σ‐phenyl protons are merged with biphenyl as well as meso ‐phenyl units, however, one of the σ‐phenyl protons distinctly resonates at 7.90 ppm.…”
Section: Figurementioning
confidence: 98%
“…Noticeably the formed bridges ((N) 2 BB(N) 2 , (N) 2 BOB(N) 2 or (N) 2 B(O) 2 B(N) 2 ) stabilize the final structures 3. A single boron complex has been reported for N‐fused porphyrins, in which the size of the coordination cavity is noticeably reduced 4. In fact the flexibility of N‐confused porphyrin,5 also observed for 21‐telluraporphyrin6 or even pentaphyrin(1.1.1.1.1),7 allows a remarkable adjustment of the macrocycle to the phosphorus cation via a fusion step as seen for 1 , 2 , and 3 , respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 95%
“…[161] Subsequent research showed that coordination of metallic and nonmetallic elements with small ionic radii is also capable of inducing ring fusion (these complexes can also be made starting directly from the fused ligand). Examples reported to date include 8b-Re(CO) 3 [167] (oxidizable to 8b-ReO 3 [168] , Figure 6), 8f-BPh + Cl À , [169] and 9f-P=O. [142] The phenylboron species, is cationic and easily undergoes nucleophilic addition at position 3, while retaining uninterrupted macrocyclic conjugation.…”
Section: N-confused and N-fused Porphyrinsmentioning
confidence: 99%